Playing in Limbo - Lora Winters; Ruth Monnier (University of Huddersfield Press, 2022)
University libraries are stereotyped as a quiet space for studying and reading in the stacks, but they can be a vibrant hub for learning and play, especially when they contain writing centers, tutoring programs, and other support structures for students. At our university, the writing center and student success office are housed in the main library location. Efforts are made by these offices to engage students, who regularly use the library to study, with their services. Due to the physical boundaries and location within the library, students seem to intentionally come to the physical location to utilize only one of the services, either the writing center, tutoring, or the library's physical space and resources. We have tried to add playful elements to the liminal space between the library and the writing center's boundaries by using a variety of attention-grabbing activities to encourage students to engage with both services and support their own well-being. While these activities generate some level of engagement, some work better than others because the activity encourages participation between students, writing center staff, and library staff. Creating elements of play with liminal space and within the library contributes to keeping the atmosphere of the library vibrant, social, and engaging.